KONDISI BIOFISIK GUNUNG TUMPA SEBAGAI TAMAN HUTAN RAYA (TAHURA) - Marwan M. Wowor; Martina A. Langi; Fabiola B. Saroinsong; Wawan Nurmawan (COCOS, 2014)
ABSTRACTMount Tumpa represents one of area of water forest (catchment area) what is remained in TownManado specified initially as protected forest of at date of 28 April 1932 broadly 215 ha, nowadayspursuant to SK.434/MENHUT-II/2013 of is date of 17 June 2013 have changed over the status becomethe Great Forest Garden ( TAHURA) broadly 296 ha. This research target to learn the last conditionbiofisik of Mount Tumpa. Biological condition includes the flora, and fauna, while physical conditionincludes to landscadearea facility, and also areatiliy . Method used in flora perception of exist in GreatForest Garden of Mount Tumpa that is band have check to systematically of the size 20 x 20 m2. Florasurvey conducted at 9 dots in Great Forest Garden of Mount Tumpa. Data presented in the form oftabulation, is hereinafter descriptive by analysed. There are 59 flora type in Great Forest Garden areaof Mount Tumpa. Most dominant flora type is Spathodea campanulata, followed by Arenga pinnata, andGarcinia sp. Great Forest Garden of Mount Tumpa own the fascination wisata in the form of beautifulviews wich are scattered in several places.Keywords : condition biofisik of mount tumpa, as great forest garden